Applicability of calcimetry in low-calcium carbonate sediments (Latin American Journal of Sedimentology and Basin Analysis, 2022)
In Earth and Environmental Sciences, pressure calcimetry is probably the most efficient and fast method to determine calcium carbonate (CaCO3) content in rocks, sediments and soils. However, measurements of low-CaCO3 samples can be less reliable by calcimetry, depending on the instrument used. This problematic is particularly relevant for sediments and soils with low content of CaCO3, very common in past and present lakes, soils and hydromorphic systems (e.g., peatbogs, mires, wetlands), where CaCO3 analysis contribute to understand water table changes, groundwater oscillation, ecology and wind-related processes, among others. In this context, this work presents a simple protocol to obtain accurate CaCO3 determinations through pressure calcimetry in low-CaCO3 samples (
Keywords: Non-calcareous sediments/soils, Pressure calcimetry, Detection/ Quantification limits, Losson- Ignition, Micromorphology